Gross and Histological Observations on Adrenal Gland of Pig - Kumar, Vishnudeo (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on adrenal glands of pig for elicited gross and histomorphological characteristics. The gross morphological observations revealed that the left adrenal gland was heavier (3.30 g) and broader (1.65 cm) than the right (2.80 g and 1.25 cm) in pig, the gland was differentiated into cortex and medulla and was completely surrounded by a dense fibrous connective tissue capsule. The greater part of gland was composed of cortical tissue. The adrenal cortex was composed of zona arcuata, zona fasciculata and zona reticularis. The medullary cells located at periphery were larger and showed follicular arrangement. However, the medullary cells found in the center of the gland were small in size.